Effect of salbutamol on pulmonary responsiveness in chronic pulmonary allergic inflammation in guinea pigs - Kasahara,D.I. (2005)
Beta-2-agonists have been widely used by asthmatic subjects to relieve their obstructive symptoms. However, there are reports that continuous use could lead to loss of bronchial protection and exacerbation of asthma symptoms. We evaluated the effect of two regimens of salbutamol administration (twice and five times a week) in a model of chronic airway inflammation in male Hartley guinea pigs (protocol starting weight: 286 ± 30 g) induced by repeated exposures to aerosols of ovalbumin (OVA). After sensitization, guinea pigs were exposed to aerosols of 0.1 mg/ml salbutamol solution twice a week (OVA + S2x, N = 7) or five times a week (OVA + S5x, N = 8). We studied allergen-specific (OVA inhalation time) and -nonspecific (response to methacholine) respiratory system responsiveness. Seventy-two hours after the last OVA challenge, guinea pigs were anesthetized and tracheostomized, respiratory system resistance and elastance were measured and a dose-response curve to inhaled methacholine chloride was obtained. Specific IgG1 was also quantified by the passive cutaneous anaphylactic technique. OVA-sensitized guinea pigs (N = 8) showed reduction of the time of OVA exposure before the onset of respiratory distress, at the 5th, 6th and 7th exposures (P < 0.001). The OVA + S2x group (but not the OVA + S5x group) showed a significant increase in OVA inhalation time. There were no significant differences in pulmonary responsiveness to methacholine among the experimental groups. OVA + S2x (but not OVA + S5x) animals showed a decrease in the levels of IgG1-specific anaphylactic antibodies compared to the OVA group (P < 0.05). Our results suggest that, in this experimental model, frequent administration of ß2-agonists results in a loss of some of their protective effects against the allergen.